2020
DOI: 10.3390/su12093724
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Devices for Educational Purposes in Compulsory Secondary Education to Improve Student’s Learning Achievements

Abstract: The number of mobiles surpassed the population of the planet in 2018. Without a doubt, they have become the tool of reference in our social life, as well as in our work and leisure, but in educational centers, they continue to be used inefficiently or are declared off limits to some classrooms. This study aims to establish the relationship that the use of mobile phones in secondary education schools may have in regard to the student’s academic performance. For this purpose, we will carry out a secondary exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…However, roughly 59% of educational centers have integrated the use of mobile phones for educational purposes into secondary school and for educational cycles [2], and their use could influence academic performance positively, regardless of the methodology used [8]. Thus, better results are observed than when using computers, due in part to ubiquity [23], and the pedagogical innovations developed [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, roughly 59% of educational centers have integrated the use of mobile phones for educational purposes into secondary school and for educational cycles [2], and their use could influence academic performance positively, regardless of the methodology used [8]. Thus, better results are observed than when using computers, due in part to ubiquity [23], and the pedagogical innovations developed [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a digital divide exists that affects vulnerable groups of disadvantaged students, students of a foreign origin, and those with special educational needs [7]. Similarly, the use of mobile devices is also promoted among secondary students [8]. However, their application for teaching and research for educational purposes remains to be limited [9].…”
Section: Information and Communication Technology (Ict) In Educationmentioning
confidence: 99%
“…The ICT training of mathematics teachers, in addition to providing training and professional development, should encourage the integration of new active methodologies in the classroom [50] and provide effective tools for learning mathematics [51]. Despite this, technological advances are a challenge for many teachers, due to the complexity of the continuously changing software [52,53]. In addition, there is the difficulty of training teachers to adapt new methodological strategies in their teaching style and to expand their ICT tool knowledge in both their personal and professional environment [54,55].…”
Section: Ict Training For Mathematics Teachersmentioning
confidence: 99%
“…Some earlier studies have identified the utilization of computer-mediated language learning as a good medium for long-term learning. Spaced repeating can assist users in building effective study patterns with an application while engaged in L2 learning [22][23][24][25][26][27]. Other studies showed more innovation, such as how to teach vocabulary to students by making lists of words more powerful and interesting through multimedia enhancement, and this was particularly applied to the English language [28][29][30].…”
Section: Introductionmentioning
confidence: 99%